Clinical predictor of postoperative hyperkalemia after parathyroidectomy in patients with hemodialysis. (May 2018) - Li, Sijia; Liu, Shuangxin; Chen, Qiuhuan; Ge, Pingjiang; Jiang, Jie; Sheng, Xiaoli; Chen, Shaohua
Abstract: Objective: Hyperkalaemia is one of the most common reasons for patients requiring emergency treatment. This study is to investigate the risk factors of postoperative hyperkalemia in renal failure patients undergoing parathyroidectomy with autotransplantation (PTXa). Methods: One hundred and eight patients [ 54 men and 54 women; age, 45.1 ± 11.1 years (mean ± SD)] with secondary hyperparathyroidism undergoing parathyroidectomy with autotransplantation were involved in this study. Laboratory chemistries (hemoglobin, fasting blood glucose, serum calcium level, alkaline phosphatase, phosphorus, parathyroid hormone) were measured before surgery. Serum potassium level was obtained before surgery and at 0 h after surgery. Results: Serum potassium level increased in 108 patients after surgery (P < 0.05). Sixteen patients (14.8%) potassium levels rose more than 6.0 mmol/L after parathyroidectomy with autotransplantation. Age and preoperative serum potassium level were significantly negative correlated with postoperative serum potassium level. Correlation analysis and receiver operating characteristic curve method confirmed that use of the preoperative serum potassium level was the primary predictor of postoperative hyperkalemia. The cutoff point for preoperative serum potassium level was 4.40 mmol/L, according to the Youden index of the receiver operating characteristic curve. Conclusions: Preoperative serum potassium increased after parathyroidectomy with autotransplantation in patients with secondary hyperparathyroidism. The preoperative serum potassium level could help the surgeon to predict postoperative hyperkalemia in case of emergency dialysis following surgery. Highlights: Preoperative serum potassium increased after parathyroidectomy in patients with secondary hyperparathyroidism. Age and preoperative serum potassium level are significantly correlated with postoperative serum potassium level. Preoperative serum potassium level >4.40 mmol/L is the most significant predictor of postoperative hyperkalemia.